Evaluation of Street Children Development Program at Setara Shelter House Semarang - Dimas Arfan Fesdyanda; Dyah Hariani; Rihandoyo Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2012)
Coaching format appropriate to the street children's needs and expectationswith respect to the factors of domestic and external factors. Among the factors in thepotential and the limitations that exist, while external factors are the opportunitiesand constraints. Effort to find a format modeled on fostering the development ofstreet children through these houses will be done by exploring the potential,weaknesses, opportunities and constraints of the problems of street children who willbe integrated with the existing pattern of approach to suit the needs and demands ofthe street children themselves. The study aims were to describe the achievement ofprogram development through Shelter Home for street children in Semarang. Todetermine the factors supporting and inhibiting formation program through a HouseShelter for street children in SemarangThe approach used in this study is descriptive qualitative data collectionmethod is observation / observation, documentation, and interviews. The gathereddata will be presented by the reduction of unnecessary data in the study. Once thatwas done inferences / verification.Based on the discussions and conclusions, the authors propose the followingrecommendations: Input, consisting of support resources and human resources.Availability of resources necessary coaching support street children in shelter homesEquivalents quite good. Process, the House dropped the equivalent of setting thework program focuses on the empowerment of street children through learning.Outputs (results), the intensity of the achievements have not been optimal, but as faras conditions permit because of the limited financial resources, human resources andmobility facilities owned houses. Outcomes (impact), viewed from the aspect ofperformance shows non optimal level of capacity or capability of a halfway houseofficers in understanding service procedures and the understanding of the socialwork profession to have an impact on the achievement of service performance.